STRATEGIC HUMAN CAPITAL, PRODUCT DIVERSIFICATION, CUSTOMER RELATIONSHIP, AND HUMAN LEARNING AS DRIVERS OF PERFORMANCE IN MANUFACTURING INDUSTRIES IN KENYA - Muriithi, Ann; Muathe, Stephen Makau (American International Journal of Social Science Research, 2023)
Strategic management is an essential element of contemporary businesses. Firms have embraced these drivers to enhance performance and competitive advantage. Constant environmental changes underline the need for strategies to respond and remain competitive. The study investigates the effect of strategic management drivers on the performance of confectionary manufacturing industries in Kenya. Strategic human capital, product diversification, customer relationship management, and organizational learning are the drivers examined. This study employed a descriptive research design to select a sample of 124 employees from the target companies. The data was analyzed using descriptive and multiple regression models. The results indicate that strategic management drivers significantly affect the performance of the confectionary manufacturing companies. The findings indicated that strategic human capital, product diversification, customer relationship management, and organization learning have a positive and significant effect on the performance of these firms. Strategic human capital and organizational learning had a significant effect, while the influence of product diversification and customer relationship management was moderate. The study concludes that strategic management drivers can help companies enhance organizational performance. The results from this study imply that companies should embrace implementing these drivers to boost performance. JEL Classification Codes: M1, L200, L66, L25, M41.